Industrial Investment Funds, Government R&D Subsidies, and Technological Innovation: Evidence From Chinese Companies - Ren, Yuan-ming (Frontiers in Psychology, 2022)
Industrial investment funds are a new financing innovation mode that can build an effective financing channel for enterprises. Based on the panel data of Chinese Listed Companies in 2008-2017, this paper constructs a static panel model between industrial investment funds, government R&D subsidies, and technological innovation to empirically analyze the effects of industrial investment fund involvement and government R&D subsidies on companies’ technological innovation. The research shows that industrial investment fund involvement can increase the company's R&D investment by providing financial funds for the company, which can effectively solve the company's lack of funds in the process of technological innovation and guarantee the smooth running of the company's innovation activities. Secondly, government R&D subsidies can alleviate the pressure of R&D investment to a certain extent, which is conducive to promoting a higher level of technological innovation in the company. Thirdly, for companies with industrial investment fund involvement, government R&D subsidies are conducive to promoting technological innovation. In contrast, for companies without industrial investment fund involvement, government R&D subsidies have no significant impact on technological innovation to a certain extent or even have a "crowding out effect."